Was there a Revival of Hebrew during the Hasmonean Period?: A Reassessment of the Evidence - Machiela, Daniel A. (Journal of ancient Judaism, 2021)
Abstract Since the end of the nineteenth century, many scholars have held that there was a revival of the Hebrew language during the Hasmonean period, associated with a growing nationalistic sentiment under Hasmonean leadership at that time. Other scholars have rejected this idea, opting instead for a revival of the language at different times, or for no revival at all. Though the idea of a national revival of Hebrew has often been used to explain various historical or literary phenomena in early Judaism, serious defenses of this position have been lacking. In this article, we examine much of the relevant literary, epigraphic, and archeological evidence in order to reassess the idea of a revival of Hebrew associated with Hasmonean rule. In light of this evidence, we conclude that such a revival finds strong literary and archaeological support, and may justifiably be assumed by historians of Second Temple period Judaism.